Actualization The Values Of Pancasila Philosophy In School: Study Of Implementation In The Curriculum And Learning To Build Student Character - Pardosi, Milton Thorman (STKIP Singkawang, 2024)
This study aims to determine the implementation of the actualization of the values of the Pancasila philosophy in schools in the curriculum and learning with the intention of forming student character. The strengthening of Pancasila needs to be carried out by grounding Pancasila through the movement to actualize the values and cultivate the Pancasila character. The method used in this research is qualitative analysis. The approach in this study uses an interdisciplinary approach. The results of this study revealed that the formation of character in students at school is an important matter by examining the contents of Pancasila which will produce a good curriculum and learning guide. Actualizing Pancasila values which contain important points in character building can help teachers achieve this goal. This can continue to be applied in civics education learning.